Is the Threat of Foreign Aid Withdrawal an Effective Deterrent to Political Oppression? Evidence from 53 African Countries - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
This study complements existing literature on the aid-institutions nexus by focusing on political rights, aid volatilities and the post-Berlin Wall period. The findings show that while foreign aid does not have a significant effect on political rights, foreign aid volatilities do mitigate democracy in recipient countries. Such volatilities could be used by populist parties to promote a neocolonial agenda, instill nationalistic sentiments and consolidate their grip on power. This is especially the case when donors are asking for standards that majority of the population do not want and political leaders are unwilling to implement them. The empirical evidence is based on 53 African countries for the period 1996-2010. As a main policy implication, creating uncertainties in foreign aid for political rights enhancement in African countries may achieve the opposite results. Other implications are discussed including the need for an `After Washington consensus'.
Keywords: C53; F35; F47; O11; O55; 330; Uncertainty; Foreign aid; Political Rights; Development; Africa